2021
DOI: 10.1002/onco.13751
|View full text |Cite
|
Sign up to set email alerts
|

Symptom Burden and Palliative Care Needs of Patients with Incurable Cancer at Diagnosis and During the Disease Course

Abstract: Background. Although current guidelines advocate early integration of palliative care, symptom burden and palliative care needs of patients at diagnosis of incurable cancer and along the disease trajectory are understudied. Material and Methods. We assessed distress, symptom burden, quality of life, and supportive care needs in patients with newly diagnosed incurable cancer in a prospective longitudinal observational multicentre study. Patients were evaluated using validated self-report measures (NCCN Distress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 42 publications
1
41
0
2
Order By: Relevance
“…Incurable cancer challenges patients to deal with physical, psychological and social symptoms, and existential concerns, affecting aspects of their health-related quality of life (HRQOL). 1 , 2 Maintaining optimal HRQOL by early identification of symptoms and providing access to palliative care services if needed, is an important aspect of palliative care.…”
Section: Introductionmentioning
confidence: 99%
“…Incurable cancer challenges patients to deal with physical, psychological and social symptoms, and existential concerns, affecting aspects of their health-related quality of life (HRQOL). 1 , 2 Maintaining optimal HRQOL by early identification of symptoms and providing access to palliative care services if needed, is an important aspect of palliative care.…”
Section: Introductionmentioning
confidence: 99%
“…The definition of tolerable tumor volume that is related to the quality of life is obscure 57 , as it is associated with multidimensional factors, such as symptom burden, age, cancer type, and patient expectations. For instance, in a longitudinal study of approximately 500 patients with different types of cancer, patients with stomach, esophageal, hepatobiliary, or head and neck cancer had higher distress levels than other patients 58 . In addition, in phase III trials of prostate cancer, it has been reported that stabilizing the symptom burden is not correlated with the survival rate 59 .…”
Section: Discussionmentioning
confidence: 99%
“…At the time of diagnosis of incurable cancer, many patients experience a high symptom burden including pain and fatigue (17)(18)(19). Nearly 80% of patients with metastatic cancer also present with symptomatic disease at the time of palliative RT consultation (20).…”
Section: Introductionmentioning
confidence: 99%